Experience of Health Workers in Efforts to Control Covid-19 - Yeni Rusyani (STIKES DUTAGAMA KLATEN, 2023)
Covid-19 is currently a serious world problem with the number of cases increasing every day. Health workers are someone who has the most contact with patients who are at risk of contracting the Covid19 virus. The majority of health workers, with large numbers in health care centers, are directly involved and in contact with patients for 24 hours. This study aims to identify the experience of health workers while providing health services to patients infected with Covid-19. Qualitative data obtained through indepth interviews with seven nurses from several hospitals in Yogyakarta. The results of the study found four main themes, namely knowledge about how to treat covid 19 patients, motivation to care for patients, psychological conditions of health workers while caring for covid 19 patients, efforts to reduce the risk of contracting and the role of health workers in providing health services to families of covid 19 patients. The results of this study concluded that there is a need for research on the Application of the Family-Centered Nursing Model to the Implementation of Family Health Tasks in Preventing the Transmission of Covid-19.